2012
DOI: 10.4172/2168-9849.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Transforming Russian Potato Cultivars for Resistance to Colorado Beetle

Abstract: Using Agrobacterium-mediated transformation procedure, a total of 204 primary transformants of the Elizaveta, Lugovskoi and Nevski potato varieties carrying the cry IIIa gene were obtained. A number of biomolecular tests, including Southern hybridization, insert copy number screening, immunofluorescence analysis for assessment of the target gene expression levels, and PCR control for testing of the insert integrity, was carried out for these transformants, as well as the biosafety field trials for the transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Thus, in this study, the transformation efficiency was 30.92%. Other researchers have reported lower numbers; for example, Guo et al (2016) reported 2.15%, while Kamionskaya et al (2012) reported 9.3% and 20.8% transformation rates for two different potato varieties.…”
Section: Pcr Analysis Of Putative Transformantsmentioning
confidence: 89%
“…Thus, in this study, the transformation efficiency was 30.92%. Other researchers have reported lower numbers; for example, Guo et al (2016) reported 2.15%, while Kamionskaya et al (2012) reported 9.3% and 20.8% transformation rates for two different potato varieties.…”
Section: Pcr Analysis Of Putative Transformantsmentioning
confidence: 89%
“…Due to their specific interactions with their membrane lipid receptor CPE, these aegerolysin-based bicomponent proteinaceous complexes might represent alternatives to currently used bioinsecticides, such as the proteinaceous crystal toxins (i.e., Cry toxins) from the bacterium Bacillus thuringiensis . Transgenic potato cultivars and corn hybrids that express Cry toxins (e.g., Bt potatoes, Bt maize) have been developed to provide resistance to CPB and WCR, and have been used in commercial cultivation in the USA since 1995 and 2003, respectively [ 11 , 12 , 13 , 14 , 15 ]. One of the Cry toxins used against WCR is the binary Cry34Ab1/Cry35Ab1 complex, where, structurally, Cry34Ab1 belongs to the aegerolysin protein family [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%